PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA DENGAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN SOFT SKILLS DAN HARD SKILLS PESERTA DIDIK SMA - Ratnaningtyas, Delthawati Isti; Wilujeng, Insih (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
The study aims to develop the physics instructional toolkit based on scientific approach which is eligible for learning and to investigate whether the physics instructional toolkit based on scientific approach developed can improve soft skills and hard skills of senior high school students. The study was conducted through a research and development adapting the Borg & Gall model. The steps of the study consisted of pre-research and collecting information, planning, developing preliminary form of product, testing preliminary field, revising main product, testing main field, and revising operational product. The data collection techniques were interview, observation, test, and questionnaire. The data were analysed by descriptive statistics and inferential statistics using MANOVA at the 0.05 significance level.The results of the study are the physics instructional toolkit based on scientific approach developed is eligible for learning based on expert judgements and the result of testing field and there is a significant difference in the mean of soft skills and hard skills gain of students between those who learned through physics instructional toolkit based on scientific approach developed and those who learned by conventional instructional toolkit.